Batik Matika Builds Critical Thinking and Geometry Problem Solving Skills: Batik Matika Membangun Kemampuan Berpikir Kritis dan Pemecahan Masalah Geometri - Fitriyah, Nur; Wiryanto, Wiryanto; Ekawati, Rooselyna (Indonesian Journal of Innovation Studies, 2025)
General Background: Developing students' critical thinking and problem-solving skills in mathematics remains a key challenge in elementary education. Specific Background: Conventional teaching methods often lack contextual and cultural relevance, limiting student engagement and conceptual understanding, particularly in geometry. Knowledge Gap: Few studies have explored culturally responsive and participatory learning approaches that effectively integrate local wisdom with pedagogical strategies to enhance mathematical thinking. Aims: This study aims to develop and evaluate the effectiveness of Batik Matika, a local culture-based learning media integrated with the Guru Kecil (Little Teacher) method, in improving fourth-grade students’ critical thinking and problem-solving skills in geometry. Results: Employing a 4D Research and Development model (Define, Design, Develop, Disseminate), the study shows that Batik Matika significantly enhances students’ mathematical performance and engagement, as evidenced by improved learning outcomes and positive student feedback. Novelty: The integration of traditional batik patterns as contextual visual aids in geometry, combined with the Guru Kecil method to promote peer teaching and collaborative learning, presents an innovative approach to culturally grounded mathematics instruction. Implications: This study highlights the potential of culturally responsive pedagogy to foster deeper mathematical understanding, active student participation, and character education, offering a replicable model for contextual learning in diverse educational settings. Highlights: Integrates local culture to enhance geometry learning. Promotes peer teaching and student collaboration. Proven effective using the 4D development model. Keywords: Batik Matika, Critical Thinking, Culturally Responsive Learning